The Importance of Instructor Clarity and Its Effect on Student Learning: Facilitating Elaboration by Reducing Cognitive Load. (1st September 2016) - Bolkan, San
Abstract : Instructors can employ a variety of effective teaching behaviors, such as those that reflect clear instruction, to increase the odds that students experience success in their courses; however, despite instructional communication scholars' theoretical understanding of why clarity should enhance student learning, empirical investigations have largely stopped short of demonstrating the link. The current study examined perceptions from 253 undergraduate students to determine how clarity may impact learning through the indirect effects of receiver apprehension and, subsequently, the deep processing of information. Results of a serial mediation analysis support the contention that an appropriate explanation for the effect of clarity on learning is that it reduces students' extraneous cognitive load, which subsequently influences their propensity to deeply process classroom information.